La dérision des euruprôktoi. Les dimensions politiques de l’aischrologia comique - Jean-Noël Allard (Cahiers Mondes Anciens)
In a few attic comedies, poets insult people who practice sodomy by calling them « wide arse », « gaping arse » or « tanked arse ». By using these aischrologia, the poets however don’t intend to denigrate a sexual practice but to express a political view. These insults target sometimes ordinary Athenians citizens, sometimes the city ruling elite, but the aim is to point out the domination of the latter over the former in order to help the Athenian demos to recover the authority democracy bestows him.